Beta‐adrenoceptor expression in pemphigus foliaceus. (29th May 2018) - Miyamoto, D.; Dias, A.B.T.; Aoki, V.; Burnier, M.N.
Abstract : Linked article: This article is commentary on by A. Abdelmaksoud et al., pp. e458–e459 in this issue. To view this article visithttps://doi.org/10.1111/jdv.15054